Estudo evolutivo do vírus dengue predominante no estado do Amazonas (2011-2016), com foco na dispersão viral e na falha no diagnóstico sorológico - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Dengue is considered one of the most important arboviruses that affects man. In Brazil, in 2017, 252,054 probable cases of dengue were reported, of which only 4,000 cases of the disease were recorded in Amazonas. However, studies have shown that factors such as circulating serotype, geographic region of patients and secondary infections may be related to decreased sensitivity of the test when compared to the molecular methods. Therefore, in order to evaluate possible mutations that may be associated with dengue dispersal in Amazonas, as well as the failure to detect the NS1 antigen, we performed this study of the evolution of the predominant dengue virus serotype/genotype in the period from 2011 to 2016 in the municipalities of the interior and in the capital of the state. A total of 608 serum samples from dengue suspects were collected from 26 municipalities in Amazonas. The samples were submitted to viral RNA extraction and later to the real-time PCR method, in which 181 (29.7%) samples had a positive result. Subsequently using a semi-nested PCR protocol, we observed the predominance of DENV-4 (N = 80), followed by DENV-2 (N = 9) and DENV-1 (N = 7). For the DENV-1 and 2 serotypes, conventional PCR and sequencing reactions were conducted only for the ENV region, whereas for DENV-4 the coding region for NS1 was also sequenced. Phylogenetic analyzes were performed according to the maximum likelihood (ML) method in the PhyML program, using the model chosen with the help of the jModeltest v2.1.7 program and Bayesian Inference using the BEAST v1.8.4 program. 27 complete sequences of ENV and 25 NS1 of DENV-4 were obtained from seven municipalities of Amazonas, all belonging to genotype II. The DENV-1 (2016) and DENV-2 (2011) sequences collected in Manaus belonged to genotype V and Asian / American, respectively. During the analysis of the DENV-4 ENV sequences, 140 variable sites and eight amino acid exchanges were found, whereas in the NS1 sequences 91 variable sites and seven amino acid exchanges were observed. According to the phylogeographic analysis, there were at least two independent entries of DENV-4 in the state of Amazonas. In addition, our data also showed the spread of DENV-4 from Manaus to other municipalities within the state of Amazonas. In the seroprevalence tests, 45% (164/360) of the samples were reagents for IgG detection, and no significant difference was observed between samples NS1-Positive (43.9%) and NS1-Negative (47.2%). We believe that this study has an important role in arboviral surveillance in the state of Amazonas, reporting not only the serotypes and genotypes of DENV from different municipalities, but also how the DENV-4 GII spread in the State.
Keywords: Dengue; Evolução viral; Proteína não estrutural 1; Amazonas; CIÊNCIAS BIOLÓGICAS